2017
DOI: 10.18632/oncotarget.19296
|View full text |Cite
|
Sign up to set email alerts
|

Addition of 2-(ethylamino)acetonitrile group to nitroxoline results in significantly improved anti-tumor activity in vitro and in vivo

Abstract: Lysosomal cysteine peptidase cathepsin B, involved in multiple processes associated with tumor progression, is validated as a target for anti-cancer therapy. Nitroxoline, a known antimicrobial agent, is a potent and selective inhibitor of cathepsin B, hence reducing tumor progression in vitro and in vivo. In order to further improve its anti-cancer properties we developed a number of derivatives using structure-based chemical synthesis. Of these, the 7-aminomethylated derivative (compound 17) exhibited signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…15 NXQ was also considered as a potent and selective inhibitor of cathepsin B, hence reducing glioma tumor progression in vitro and in vivo, and a number of derivatives of NXQ were developed by using structure-based chemical synthesis in order to further improve its antitumor properties. 16,17 In this study, NXQ was found to suppress SCLC cell survival and induce SCLC cell apoptosis (Figures 1 and 2). These above indicated that it was conceivable that the widely used antibacterial agent NXQ might be tried for SCLC treatment in clinic.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…15 NXQ was also considered as a potent and selective inhibitor of cathepsin B, hence reducing glioma tumor progression in vitro and in vivo, and a number of derivatives of NXQ were developed by using structure-based chemical synthesis in order to further improve its antitumor properties. 16,17 In this study, NXQ was found to suppress SCLC cell survival and induce SCLC cell apoptosis (Figures 1 and 2). These above indicated that it was conceivable that the widely used antibacterial agent NXQ might be tried for SCLC treatment in clinic.…”
Section: Discussionmentioning
confidence: 57%
“…In cholangiocarcinoma cells, NXQ also exhibited anticancer activity by inducing FoxM1 inhibition . NXQ was also considered as a potent and selective inhibitor of cathepsin B, hence reducing glioma tumor progression in vitro and in vivo, and a number of derivatives of NXQ were developed by using structure‐based chemical synthesis in order to further improve its antitumor properties . In this study, NXQ was found to suppress SCLC cell survival and induce SCLC cell apoptosis (Figures and ).…”
Section: Discussionmentioning
confidence: 93%
“…tumor growth compared to the nitroxoline (Mitrović et al, 2017). Taken together these results show that the nitroxoline scaffold can be used as a starting point for the synthesis of novel compounds with improved pharmacological characteristics (Mitrović et al, 2017).…”
Section: Nitroxoline Derivativesmentioning
confidence: 78%
“…Nitroxoline derivatives were prepared with the aim of improving its activity against cathepsin B (Mirković et al, 2011;Sosič et al, 2013Sosič et al, , 2018Mitrović et al, 2017). Evaluation of new compounds with structural modifications on various positions of the nitroxoline scaffold revealed the structural requirements for cathepsin B inhibition (Mirković et al, 2011;Sosič et al, 2013Sosič et al, , 2018Mitrović et al, 2016Mitrović et al, , 2017. The nitro group at position 5 of nitroxoline was identified as essential for nitroxoline binding to cathepsin B, its absence resulting in loss of cathepsin B inhibition.…”
Section: Nitroxoline Derivativesmentioning
confidence: 99%
See 1 more Smart Citation